Functional missense and splicing variants in the retinoic acid catabolizing enzyme CYP26C1 in idiopathic short stature - Montalbano, Antonino; Jürgensen, Lonny; Röth, Ralph; Weiß, Birgit; Hassel, David; Rappold, Gudrun (European journal of human genetics, 2018)
Height is a complex quantitative trait with a high heritability. Short stature is diagnosed when height is significantly below the average of the general population for that person’s age and sex. We have recently found that the retinoic acid degrading enzyme CYP26C1 modifies SHOX deficiency phenotypes toward more severe clinical manifestations. Here, we asked whether damaging variants in CYP26C1 alone could lead to short stature. We performed exome and Sanger sequencing to analyze 856 individuals with short stature where SHOX deficiency was previously excluded. Three different damaging missense variants and one splicing variant were identified in six independent individuals; the functional significance of the identified variants was tested in vitro or in vivo using zebrafish as a model. The genetic and functional data reported here indicate that CYP26C1 represents a novel gene underlying growth disorders and that damaging variants in the absence of SHOX variants can lead to short stature.